Future scenarios and opportunities for interventional radiology in the post COVID-19 era - Jose Maria Abadal; Jimena Gonzalez-Nieto; Fernando Lopez-Zarraga; Miguel Angel de Gregorio; Panagiotis M. Kitrou; Santiago Mendez (Diagnostic and Interventional Radiology, 2021)

(untitled)
Pandemic outbreak has led health systems worldwide into a rapid reorganization in response to coronavirus infections, forcing interventional radiology units to adapt. Interventional procedures have evolved in number, type and setting and have arguably been optimized as a direct consequence of this pandemic; a result that will undoubtedly lead to radical change within the specialty. This paper explores the future of interventional radiology from various perspectives, and forecasts the new opportunities that will be presented, from the adaptation of the interventional radiology staff and angiography suite, to the immunological environment, and through to digital medical education. We analyze the economic impact and the future relationship we can expect with the rest of the medical industry.